Hybrid photovoltaic-thermal solar systems for combined heating, coolingand power provision in the urban environment - Ramos,Cabal A; Chatzopoulou,MA; Guarracino,I; Freeman,J; Markides,CN (Energy Conversion and Management, 2017)
Solar energy can play a leading role in reducing the current reliance on fossil fuels and in increasing renewable energy integration in the built environment. Hybrid photovoltaic-thermal (PV-T) systems can reach overall efficiencies in excess of 70%, with electrical fficiencies in the range of 15-20% and thermal efficiencies of 50% or higher. In most applications, the electrical output of a hybrid PV-T system is the priority, hence the contacting fluid is used to cool the PV cells to maximise their electrical performance, which imposes a limit on the fluid's downstream use. When optimising the overall output of PV-T systems for combinedheating and cooling provision, this technology can cover more than 60% of the heating and about 50% of the cooling demands of households in the urban environment. To achieve this, PV-T systems can be coupledto heat pumps or absorption refrigeration systems as viable alternatives to vapour-compression systems. This work considers the techno-economic challenges of such systems, when aiming at a low cost per kWh of energy generation of PV-T systems for co- or tri-generation in the housing sector. First, the viability and afordability of the proposed systems are studied in ten European locations, with local weather pro files, using annually and monthly averaged solar-irradiance and energy-demand data. Based on annual simulations, Seville, Rome, Madrid and Bucharest emerge as the most promising locations from those examined, and the most efficient system confi guration involves coupling PV-T panels to water-to-water heat pumps that usethe PV-T thermal output to maximise the system's COP. Hourly resolved transient models are then defi ned in TRNSYS in order to provide detailed estimates of system performance, since it is found that the temporal resolution (e.g. hourly, daily, yearly) of the simulations strongly affects their predicted performance. The TRNSYS results indicate that PV-T systems have the potential to cover 60% of the heating